The effect of E-CRM features on customers satisfaction for airline e-ticket services in Malaysia - Ismail, Nor Alina; Hussin, Husnayati (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Recently, the use of technology is growing fast and most of industries apply technology in their business including Airline Industry. The improvement of technology world has forced airline companies into hard competition among them. E-ticket help to ease the process of online transaction between company and customer. This study examines the esatisfaction of using airlines e-ticketing system in Malaysia based on customers point of view. Using the survey questionnaire method, more than 500 questionnaire were distributed and 508 were used for analysis. In order to get the hypotheses results, the SEM analysis technique has been applied to this study. The target respondent for this study is among internet users who had used any Malaysia airlines eservices. Finding indicate that e-CRM pre-purchase and postpurchase have a positive effect on customer satisfaction and have a positive significant relationship. This finding reveals that most of the respondents are satisfied with the e-services provided by airlines in Malaysia and this level of customer satisfaction will lead to loyalty and indirectly the both customer and company is developing the long-term relationship.